2017
DOI: 10.1371/journal.pone.0174782
|View full text |Cite
|
Sign up to set email alerts
|

Relative abundance of total subgingival plaque-specific bacteria in salivary microbiota reflects the overall periodontal condition in patients with periodontitis

Abstract: Increasing attention is being focused on evaluating the salivary microbiota as a promising method for monitoring oral health; however, its bacterial composition greatly differs from that of dental plaque microbiota, which is a dominant etiologic factor of oral diseases. This study evaluated the relative abundance of subgingival plaque-specific bacteria in the salivary microbiota and examined a relationship between the abundance and severity of periodontal condition in patients with periodontitis. Four samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 23 publications
4
50
1
1
Order By: Relevance
“…High levels of JP2 genotype A. actinomycetemcomitans in saliva may be a risk factor for disease onset but could also be a result of release of bacteria from diseased pockets. It has previously been shown that the presence of periodontal pathogens in subgingival plaque correlate with that found in saliva; however, these data were semiquantitative without specific quantification (Haririan et al, ; Kageyama et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…High levels of JP2 genotype A. actinomycetemcomitans in saliva may be a risk factor for disease onset but could also be a result of release of bacteria from diseased pockets. It has previously been shown that the presence of periodontal pathogens in subgingival plaque correlate with that found in saliva; however, these data were semiquantitative without specific quantification (Haririan et al, ; Kageyama et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Treatment of AgP also resulted in greater shifts in the composition of the subgingival microbiota, compared to the salivary microbiome, [ 28 ] but the relative taxonomic abundances of the two microbiomes appear to correlate well with one another treatment. [ 8–10 ] In addition, the salivary microbiome has the potential to discriminate between treated and well‐maintained periodontitis versus pristine periodontal health, suggesting that certain inherent features may identify periodontitis‐susceptible individuals, despite clinical disease resolution. [ 10 ] One should also consider that sampling of the salivary microbiome may be more homogenous and repetitive among studies.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8–10 ] In addition, the salivary microbiome has the potential to discriminate between treated and well‐maintained periodontitis versus pristine periodontal health, suggesting that certain inherent features may identify periodontitis‐susceptible individuals, despite clinical disease resolution. [ 10 ] One should also consider that sampling of the salivary microbiome may be more homogenous and repetitive among studies. [ 7 ] Variations between studies on subgingival microbiomes may occur due to procedural differences in biofilm sampling (curette versus paper‐point), [ 29,30 ] or may indeed reflect highly specific biological differences between affected sites.…”
Section: Discussionmentioning
confidence: 99%
“…Ion Torrent 16S rRNA gene amplicon sequencing 16S rRNA gene amplicon sequencing analyses were performed as previously described (22). In brief, the V1-V2 regions of the 16S rRNA gene in each sample were amplified using the following primers: 8F (5′-AGA GTT TGA TYM TGG CTC AG-3′) with the Ion Torrent adaptor A and a sample-specific 8-base tag sequence, and 338R (5′-TGC TGC CTC CCG TAG GAG T-3′) with the Ion Torrent adaptor trP1.…”
Section: Bacterial Quantification Via Real-time Pcrmentioning
confidence: 99%